Об этнической атрибуции могильника Узен-Баш - Айбабина, Е.А. (Материалы по археологии, истории и этнографии Таврии, 1993)
Могильник Узень-Баш находится в Байдар- ской долине рядом с селом Родниковым (бывшее Скеля), на склоне горы у истока Черной Речки. Этническая принадлежность погребальных сооружений могильника Узень-Баш в литературе определялась по-разному. Большой интерес представляют хранящиеся- в Архиве ЛОИА АН СССР и Крымском краеведческом музее материалы раскопок не разрушенных склепов могильника Узень-Баш, раскопанных Н. Л. Эрнстом в 1927 г. Публикации этих материалов и посвящена данная работа. This article is devoted to the question of ethnic affiliation of Uzen-Bash cemetery in the South-Western Crimea, several vaults of which were unearthed in 1907 and 1926. The materials of N. L. Ernst's excavations are published for the first time. The investigated part of the cemetery is dated by the second quarter of the 7th — the end of the 9th century. The inventory of the burials contains things of Byzantine and several isolated finds of Saltovo cultures. The construction of vaults is connected with the Late Scythian vaults in the Crimea, and were built, probably, by the descendants of the Scythian population, assimilated by Sarmatians-Alans.